2009
DOI: 10.1111/j.1525-139x.2009.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond The Current Paradigm: Recent Advances in The Understanding of Sodium Handling – Guest Editors: Stanley Shaldon and Joerg Vienken: Water‐Free Sodium Accumulation

Abstract: The widely accepted concept of body fluid and electrolyte homeostasis is that Na(+) is restricted mainly to the extracellular fluid and K(+) to the intracellular space, where both ions act to hold water and thereby control the extracellular and intracellular fluid volume by their osmotic activity. Na(+) accumulation thus inevitably leads to water retention. The constancy of the extracellular volume is the task of the kidneys, which control the total body Na(+) content. More recent data have questioned this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 17 publications
(24 reference statements)
2
43
0
1
Order By: Relevance
“…The relationship between sodium and BP in HD patients is more complicated than mere volume expansion. Previous models of sodium kinetics assume a two-compartment model, but Titze [17] has recently proposed an alternative threecompartment model by showing that sodium can accumulate in the vascular wall without volume expansion, which might explain the lag in improved BP control seen after dry weight reduction in patients treated with longslow HD [17,32,33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between sodium and BP in HD patients is more complicated than mere volume expansion. Previous models of sodium kinetics assume a two-compartment model, but Titze [17] has recently proposed an alternative threecompartment model by showing that sodium can accumulate in the vascular wall without volume expansion, which might explain the lag in improved BP control seen after dry weight reduction in patients treated with longslow HD [17,32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible for patients to load sodium during dialysis, despite dialysate sodium concentration being lower than the predialysis plasma sodium concentration (commonly termed 'low' dialysate sodium concentration) [15,16] . More recently, the non-osmotic storage of sodium in skin and other tissues has been described and this may further allow dissociation of sodium and water handling [17] . Though the effects of this may be negligible over a single HD session, the potential of this reservoir of sodium ions to buffer sodium transport over a longer period and influence BP and IDWG has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It assumes isosmolarity of body fluids among the bodily compartments (2). Along with others (4-7), we (8)(9)(10)(11)(12)(13)(14) showed earlier that electrolytes are distributed in a more complex 3-compartment model, in which intravascular and the interstitial fluids do not equilibrate as readily as believed (15,16). We underscored the importance of Na + binding to negatively charged proteoglycans in the skin, the largest organ with the most extracellular space (8,11).…”
Section: Introductionmentioning
confidence: 92%
“…Titze,18 who suggested that Na + handling during increased dietary salt intake is more complex, highlighting the dynamic role of the dermal interstitium as a reservoir that can buffer the impact of Na + accumulation on the intravascular volume and blood pressure, proposed that accumulated water-free Na + is associated with hypertension. However, the relationship between vascular injury and water-free Na + remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%